2022
DOI: 10.3390/antiox11071272
|View full text |Cite
|
Sign up to set email alerts
|

The Synergetic Effect of Egyptian Portulaca oleracea L. (Purslane) and Cichorium intybus L. (Chicory) Extracts against Glucocorticoid-Induced Testicular Toxicity in Rats through Attenuation of Oxidative Reactions and Autophagy

Abstract: Long-term glucocorticoids can alter sperm motility, vitality, or morphology, disrupting male reproductive function. This study scrutinized the synergistic benefits of two Egyptian plants against dexamethasone (Dexa)-induced testicular and autophagy dysfunction in male rats. Phytochemical ingredients and the combination index were estimated for Purslane ethanolic extract (PEE) and Chicory water extract (CWE). Four control groups received saline and 100 mg/kg of each PEE, CWE, and PEE/CWE, daily for 8 weeks. Dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 129 publications
(179 reference statements)
0
1
0
Order By: Relevance
“…Saleh et al showed that administration of ethanolic extract of P. oleracea (100 mg/kg) and Chicory water extract (100 mg/kg) in rats with testicular and autophagy dysfunction synergetically improved testicular toxicity via reducing MDA and enhancing GSH, GST, and GPx activities [ 133 ]. Similarly, in the rat model of testicular toxicity induced by acrylamide, oral administration of 200 and 400 mg/kg P. oleracea extract improved testicular toxicity through reduction of oxidative status [ 134 ].…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…Saleh et al showed that administration of ethanolic extract of P. oleracea (100 mg/kg) and Chicory water extract (100 mg/kg) in rats with testicular and autophagy dysfunction synergetically improved testicular toxicity via reducing MDA and enhancing GSH, GST, and GPx activities [ 133 ]. Similarly, in the rat model of testicular toxicity induced by acrylamide, oral administration of 200 and 400 mg/kg P. oleracea extract improved testicular toxicity through reduction of oxidative status [ 134 ].…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…[26]. Chicory roots contain a variety of bioactive compounds, including alkaloids, flavonoids, phenolics, inulin, tannins, saponins, sesquiterpene lactones, chlorophyll pigments, unsaturated sterols, and coumarins, that are beneficial to humans [27,28]. Chicory root water extract was reported to contain large amounts of polyphenols, resveratrol, and naringin.…”
Section: Introductionmentioning
confidence: 99%
“…Chicory root water extract was reported to contain large amounts of polyphenols, resveratrol, and naringin. Chicory exhibits a wide range of biological effects, including anti-inflammatory, antioxidant, hepatoprotective, immune, cardiovascular, hypolipidemic, antidiabetic, anticancer, gastro-protective, antibacterial, and many others [26,28]. Due to its high inulin concentration, chicory promotes calcium absorption, increases bone mineral content (BMC), and slows the loss of bone mineral density (BMD) [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations